EPIDEMIOLOGICAL PROFILE OF TYPE 2 DIABETIC PATIENTS (DM2) IN THE FAR WEST MESOREGION OF BAHIA - Alves, Maciel Santos Oliveira; Picinato, Maria Cecilia (Seven Editora, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic non-communicable disease with a globally increasing prevalence, representing a serious public health challenge due to associated risk factors such as overweight and obesity. This study aimed to analyze the epidemiological profile of patients with T2DM in the mesoregion of the extreme west of Bahia, Brazil. The sample consisted of 140 patients with T2DM from two healthcare units in the city of Barreiras-BA, including both sexes aged 40 years or older. The data indicate that the disease primarily affects elderly individuals, with a predominance of females, and is associated with a high prevalence of overweight and comorbidities. Therefore, a correlation was concluded between the epidemiological profile of these individuals with T2DM and the chronic complications associated with this disease in the population of western Bahia.DOI: https://doi.org/10.56238/sevened2025.037-004